2020
DOI: 10.3390/ijms21082908
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine in Childhood Asthma: Omic Studies of Treatment Response

Abstract: Asthma is a heterogeneous and multifactorial respiratory disease with an important impact on childhood. Difficult-to-treat asthma is not uncommon among children, and it causes a high burden to the patient, caregivers, and society. This review aims to summarize the recent findings on pediatric asthma treatment response revealed by different omic approaches conducted in 2018–2019. A total of 13 studies were performed during this period to assess the role of genomics, epigenomics, transcriptomics, metabolomics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 85 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…Recent advances in AI technologies, such as machine learning and deep learning, have further increased enthusiasm about the prospects of precision medicine transforming healthcare [ 4 , 5 , 6 , 7 , 8 , 9 ]. In pediatrics, AI-driven technologies are beginning to enter clinical studies in the management of diabetes mellitus [ 10 ], asthma [ 11 ], and cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in AI technologies, such as machine learning and deep learning, have further increased enthusiasm about the prospects of precision medicine transforming healthcare [ 4 , 5 , 6 , 7 , 8 , 9 ]. In pediatrics, AI-driven technologies are beginning to enter clinical studies in the management of diabetes mellitus [ 10 ], asthma [ 11 ], and cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To attribute remission, it was permitted to taper the research drug to a dosage of zero (by stepwise decreases from 100% to 50% to 0%), in accordance with predefined methods. The resumption of the full dosage of the research medicine was guided by algorithms [15].…”
Section: Randomizationmentioning
confidence: 99%
“…Genome‐wide association studies and candidate gene investigations have identified polymorphisms associated with asthma and acute asthma exacerbations (4). Systems biology has provided insight into the integrated function of these genetic variations and allows this to be assessed in intact individuals.…”
Section: Asthmamentioning
confidence: 99%